2015
DOI: 10.1890/es15-00037.1
|View full text |Cite
|
Sign up to set email alerts
|

Does wildfire likelihood increase following insect outbreaks in conifer forests?

Abstract: Abstract. Although there is acute concern that insect-caused tree mortality increases the likelihood or severity of subsequent wildfire, previous studies have been mixed, with findings typically based on standscale simulations or individual events. This study investigates landscape-and regional-scale wildfire likelihood following outbreaks of the two most prevalent native insect pests in the US Pacific Northwest (PNW): mountain pine beetle (MPB; Dendroctonus ponderosae) and western spruce budworm (WSB; Chorist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 53 publications
3
60
2
Order By: Relevance
“…Therefore, our metrics may identify forested areas vulnerable to beetle attack due to the presence of drought-stressed trees (Boone, Aukema, Bohlmann, Carroll, & Raffa, 2011;Breshears et al, 2005), but do not necessarily represent forest vulnerability to aggressive bark beetle outbreaks in which healthy trees may be killed (Raffa et al, 2008). This is unlikely to have a strong impact on estimated fire vulnerability because wildlife likelihood does not consistently increase or decrease following insect outbreaks (Hicke, Johnson, Jane, & Preisler, 2012;Meigs et al, 2015). This is unlikely to have a strong impact on estimated fire vulnerability because wildlife likelihood does not consistently increase or decrease following insect outbreaks (Hicke, Johnson, Jane, & Preisler, 2012;Meigs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our metrics may identify forested areas vulnerable to beetle attack due to the presence of drought-stressed trees (Boone, Aukema, Bohlmann, Carroll, & Raffa, 2011;Breshears et al, 2005), but do not necessarily represent forest vulnerability to aggressive bark beetle outbreaks in which healthy trees may be killed (Raffa et al, 2008). This is unlikely to have a strong impact on estimated fire vulnerability because wildlife likelihood does not consistently increase or decrease following insect outbreaks (Hicke, Johnson, Jane, & Preisler, 2012;Meigs et al, 2015). This is unlikely to have a strong impact on estimated fire vulnerability because wildlife likelihood does not consistently increase or decrease following insect outbreaks (Hicke, Johnson, Jane, & Preisler, 2012;Meigs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is expected that surface fires will be more likely to spread into the canopy during the gray stage [85] and salvage logging is a recommended method of forest management to reduce the fire hazard [80][81][82]. However, MPB and its impacts on fuel accumulation and subsequent fire hazard are poorly understood: some studies have suggested higher probability or severity of fire following beetle outbreak [66,79,80], while others suggest a decreased fire probability [2,86], or no evidence of any relationship between MPB and active fire [34][35][36][87][88][89]. Based on an extensive literature review, Jenkins et al [80] concluded that both rates of fire spread and fire-line intensities were higher in the current outbreak's stands than in endemic stands.…”
Section: Forest Firementioning
confidence: 99%
“…Likewise, a recent study in western USA claimed that the observed effect of MPB infestation on the area burned in 2002-2013 appears negligible at broad spatial extents [36]. Meigs et al [89] claimed that following MPB outbreak, fire likelihood is neither higher nor lower than in non-MPB-affected forests in the Pacific Northwest of USA. Many studies emphasize the importance of climate rather than fuels as the primary driver of wild fires [34,35,87,90].…”
Section: Forest Firementioning
confidence: 99%
“…Trends of increasing area burned in the western United States have been blamed on various factors, but rigorous attribution has yet to materialize. For example, outbreaks of native bark beetles (which are also triggered by warm/dry climate conditions) are routinely blamed for many recent forest fires, although scientific evidence has found weak to nonexistent links between beetle outbreaks and subsequent fire occurrence (13), area burned (14), and burn severity (15). A second common assertion is that past forest management (particularly on public lands) is to blame for recent increases in fire activity.…”
mentioning
confidence: 99%